Adipocyte Metabolism and Insulin Signaling Perturbations: Insights from Genetics. (June 2019) - Friesen, Max; Cowan, Chad A.
Abstract : Insulin resistance (IR) is a rapidly growing pandemic. It poses an enormous health burden given its comorbidity with obesity, type 2 diabetes (T2D), and other metabolic and cardiovascular diseases (CVDs). Adipose tissue has been established as a key regulator of whole-body metabolic homeostasis, with interest growing rapidly. Emerging evidence suggests that adipocytes play an important role in these afflictions and contribute to IR. Genome-wide association studies (GWAS) have begun to illuminate the genetics underlying obesity, T2D, and IR, and this will allow further study into the disease mechanisms of the genes implicated in these metabolic diseases. Progress towards understanding the molecular mechanisms underlying diseased adipocytes will be discussed here, with an eye towards the future in developing novel therapeutics to combat metabolic disease. Highlights: Insulin resistance has emerged as a main driver behind type 2 diabetes, obesity and cardiovascular disease. This has become an epidemic creating a significant burden on the healthcare system and economy around the world. The genetic underpinnings of insulin resistance are heavily under investigation and have been partly elucidated over the past few years. Many GWAS have been undertaken to identify variants associated with BMI, obesity, insulin response, cardiovascular disease and glycemic traits. Metabolic signatures of insulin resistance have been discovered, spurring more research into identifiable biomarkers for early diagnosis. Endocrine hormones and circulating factors can be measured and studied for their role in IR progression. Therapeutics targeting IR and metabolic disease are starting to be developed with the prospect of helping millions of people.